2022
DOI: 10.1021/jacs.1c13555
|View full text |Cite
|
Sign up to set email alerts
|

Histone H2B Deacylation Selectivity: Exploring Chromatin’s Dark Matter with an Engineered Sortase

Abstract: We describe a new method to produce histone H2B by semisynthesis with an engineered sortase transpeptidase. N-Terminal tail site-specifically modified acetylated, lactylated, and β-hydroxybutyrylated histone H2Bs were incorporated into nucleosomes and investigated as substrates of histone deacetylase (HDAC) complexes and sirtuins. A wide range of rates and site-specificities were observed by these enzyme forms suggesting distinct biological roles in regulating chromatin structure and epigenetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 40 publications
(74 reference statements)
1
28
0
Order By: Relevance
“…8a-b ). H2BNTac is increased by class I deacetylases inhibitors in vivo and HDAC1/2 can deacetylate it in vitro 19,29 . We tagged endogenous HDAC1/2 with GFP-FKBP 12F36V , depleted HDAC1/2- GFP-FKBP 12F36V using the dTAG approach 30 , and confirmed that H2BNTac is deacetylated by HDAC1/2 ( Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8a-b ). H2BNTac is increased by class I deacetylases inhibitors in vivo and HDAC1/2 can deacetylate it in vitro 19,29 . We tagged endogenous HDAC1/2 with GFP-FKBP 12F36V , depleted HDAC1/2- GFP-FKBP 12F36V using the dTAG approach 30 , and confirmed that H2BNTac is deacetylated by HDAC1/2 ( Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 120 Most recently this approach has been used by Wang et al in combination with a HPXTG-specific sortase to generate a wide range of engineered histone H2B variants with complexly modified N-termini. 121 …”
Section: Substrate Engineering To Enhance Product Yieldmentioning
confidence: 99%
“…A recent study showed that, out of six HDAC1-containing nuclear complexes, only the mitotic deacetylase complex (MiDAC) and the arginine-glutamic acid dipeptide repeats (RERE) could remove K(L-la) marks from histone H2B lysine 11 (H2BK11) on nucleosomes in vitro. 24 Importantly, HDAC1-3 are targets of approved cancer chemotherapy and histone K(L-la) accumulation might therefore be involved in the observed epigenetic effects of HDAC inhibitors. 4,25 Sirtuins 1 and 2 are poor delactylases on peptide substrates, with catalytic efficiencies ~1000 times lower than that of HDAC3, 26 but they can remove K(L-la) modifications from histones upon extended incubation times.…”
Section: L-lactylationmentioning
confidence: 99%
“…3 More recently, we interrogated the activity of HDAC3 using diastereomerically pure substrates and found a clear preference for K(D-bhb) modifications compared to K(L-bhb) in vitro (~12 times higher kcat/KM). 4 Similar to K(L-la), there are multiple deacylases in the cell that are capable of removing K(D/Lbhb); HDAC1-3 and SIRT1/2 show activity on extracted histones, 9 the MiDAC complex presents activity on nucleosomes bearing H2BK11(D-bhb), 24 and HDAC1-3 are the most efficient de-b-hydroxybutyrylases in the cell. 9 However, it is often unclear to what extent these activities serve as regulatory mechanisms of K(D-bhb) modifications in vivo.…”
Section: D-b-hydroxybutyrylationmentioning
confidence: 99%